Effective Preparation of One‐Dimensional Boron‐Nitride‐ Nanotube‐Supported Nanosheet Hierarchical Structures and Their Optical/Adsorption Properties. Issue 39 (22nd October 2018) - Wang, Jilin; Ji, Yuchun; Gu, Yunle; Liao, Hejie; Yang, Liuzhong; Long, Fei; Zhou, Bing; Wang, Weimin; Fu, Zhengyi
Abstract: A novel boron nitride nanotube‐supported nano‐sheets one‐dimensional hierarchical structures (BNNT‐BNNS) were efficiently prepared via a ball milling assisting chemical vapor deposition method. X‐ray powder diffraction (XRD), fourier transform infrared spectrometer (FTIR), Raman, field scanning electron microscopy (FSEM), energy dispersive spectroscopy (EDX), transmission electron microscopy (TEM) and high‐resolution transmission electron microscopy (HRTEM) were used to characterize the as‐synthesized samples. The samples presented a length of more than 20 μm and wide diameter ranges from 20 nm to 600 nm. Abundant nano‐sheets grew in random directions and intertwined closely on the surface of the one‐dimensional structures. Every nano‐sheet was transparent and demonstrated a thickness of less than 10 nm with irregular size and shape. Ultraviolet‐visible (UV‐vis) and photoluminescence (PL) results indicated that the band gap was 5.71 eV and the maximum fluorescence emission peak was located at 368 nm. In addition, it was worth noting that the BNNT‐BNNS hierarchical structures also presented excellent adsorption property for methylene blue (MB). When the adsorption time was 5 min, MB could be removed by 75.2% from water solution. The adsorption rate could increase to 97.3% when the adsorption time was 115 min. Finally, the possible chemical reactions and the corresponding catalytic cracking growth mechanism of the special hierarchical structures also were investigated carefully. Abstract : One‐dimensional boron nitride nanotube‐supported nano‐sheets hierarchical structures (BNNT‐BNNS) were prepared by a ball milling assisting chemical vapor deposition method. The band gap was 5.71 eV and the maximum fluorescence emission peak was located at 368 nm. MB could be removed by 75.2% when the adsorption time was 5 min. Possible chemical reactions and catalytic cracking growth mechanism of the samples were also proposed.